CODESRIA Bulletin Online, No. 22, July 2021 - Liberating Democracy and Democratising Liberation: Distinguished Nyerere Lecture 2021 - Shivji, Issa G. (CODESRIA Bulletin, 2021)
Mr Vice-Chancellor, Nyagoda wa Kigoda cha Mwalimu, Professor Rwekaza Mukandala, My distinguished academic colleagues and friends: History is full of ironies. Some ten years ago, Professor Mukandala was the vice-chancellor. I was the first Nyagoda of Kigoda Cha Mwalimu Nyerere. Now we both have graduated. He is the third Nyagoda while I am the Distinguished Nyerere Lecturer. It is indeed a great honour to be invited to give this lecture. Professor Mukandala wanted me to say something about democracy. I gave it a nuance and elegance: Liberating Democracy and Democratising Liberation. Now I realise that even this title does not quite capture what I want to say. But as a working title for a work in progress, it will do. My thesis in this three-part lecture is simple. It can be summed up in two short sentences. The struggle for human freedom is epochal. The struggle for democracy is episodic. I have thus titled the three parts as: Part I: Freedom and Democracy; Part II: Freedom and Liberation; and Part III: Freedom and Intellectuals. Part I: Freedom and Democracy Democracy is in prison. It has been taken hostage by party pundits, handcuffed by neoliberal ideology and mutilated by the barbaric capitalist system. What was supposed to be a stop on the long journey of human freedom was turned into a final destination by the bourgeoisie. As all hegemonic classes do, they universalised their vision of the future, their ideology and their interests, and made it applicable to all peoples at all times. Scholars and intellectuals like us have become the handmaidens of converting the particular into the universal. So now we are told there is a universal model of democracy that all of us should endeavour to attain. We are judged by this model; we are condemned by this model; we are elevated by this model; and we are downgraded by this model. The epistemology of this universal model is the atomised individual, the Robinson Crusoe. Its origin is in Western Europe, and its monstrous outgrowth is the United States. Its genesis lies in the struggles waged by labour against capital. Its achievements, among which are the fundamental freedoms to think and express and to associate freely, are the fruits of the incessant struggle of labour against capital. These achievements are not because of capital, they are in spite of it. Driven by the insatiable hunger for accumulation, capital has devastated nature and decimated peoples. Flora and fauna, mountains and minerals, rivers and lakes, oceans and seas, climate and atmosphere—nothing, absolutely nothing, is out of the reach of capital. In its drive for accumulation, capital respects nothing, least of all freedom and democracy. Big capital has no purchase on liberal democracy. Fascism in the last century was an outgrowth of monopoly capital, so is the neofascism of the neoliberal era. Modi’s Hindutva regime is beholden to big business, such as Reliance, Tata, Essar and Infosys. So is Bolsonaro of Brazil. In Africa, where states and local bourgeoisies are weak, local big business does not have much clout. Most of the time it is compromised by foreign big capital. It curries favour with the state. It thus becomes the boot-licker of whatever regime—democratic, fascist, neofascist or military—is in power using the fig-leaf of parochial ideologies of race, ethnicity and uzawa (indigeneity). Democracy is about freedom. It is not about forms of government. Forms of government (call them what you may—bourgeois democracy, national democracy, people’s democracy, proletarian dictatorship), they are all terrains of struggle that humankind forges in its quest for freedom. Those who equate democracy with freedom end up chaining freedom. We need to free freedom from democracy. Human beings are energised and mobilised by calls for freedom, not democracy. In his historic speech, ‘I have a Dream’,2 made two generations ago in 1963, Martin Luther King’s refrain was from an old AfricanAmerican spiritual: ‘Free at Last’. Malcolm X (1925–1965), a more militant African-American fighter, fought for freedom from white supremacy. ‘If you’re not ready to die for it, put the word “freedom” out of your vocabulary’, Malcolm said.3 Indeed, no one gives you freedom on a silver platter. In the eloquent words of the former slave and great African-American freedom fighter of the nineteenth century, Frederick Douglass (1817–1895), wanting freedom without struggle is like wanting ‘crops without plowing land’, is like wanting ‘rain without thunder and lightning’.4 Power concedes nothing without a struggle. Historically, the emergent bourgeoisie encapsulated its form of government in liberal democracy. Working people in their quest for freedom desired to go beyond. They attempted it in the Paris Commune of 1871. They attempted to break the chains of unfreedom. In the Commune there were no governors and governed, there were no rulers and ruled, there were no administrators and administered, there were no uniformed armed men and civilians. All Communards were both at the same time. The Commune lasted for seventy-two days. It was decisively crushed by the forces of unfreedom. Communards were outnumbered one to ten, but they fought heroically. They were fighting for a cause, the cause of creating a New World, the cause of human freedom. Since then, the Paris Commune has become a standard—a model, if you like—of the fight for freedom that goes beyond the so-called freedoms of liberal democracy. As one of the stanzas of ‘The Internationale’, which was written by a Communard, says: There are no supreme saviors Neither God, nor Caesar, nor tribune. Producers, let us save ourselves Decree on the common welfare That the thief return his plunder, That the spirit be pulled from its prison5 Let the spirit of freedom be pulled from its prison of liberal democracy. The freedom that is proclaimed here goes beyond liberal freedoms that have been captured by the legal language of rights. To quote a line from ‘The Internationale’ again, in a liberal democracy, ‘The state represses and the law cheats’. And that brings me to the question of how the constitutional and legal architecture of a liberal democracy chains rather than frees freedom from the hegemonic tentacles of capitalist relations. ***** How does the law cheat? Law is one of the ‘greatest’ inventions of the bourgeoisie. It cheats and charms at the same time. It promotes social inequality while preaching legal equality. Both a beggar and a billionaire are equal in the eyes of law, for the eyes of Lady Justice are blindfolded. Law is premised on rights. Law arrests freedom and converts it into the language of equal rights. Rights belong to the individual. The individual being is abstracted from the social being. Even freedom becomes a right—the right to freedom. The struggle for freedom, which is in a constant state of flux, is frozen in the legal regime in service of the status quo. Law is the driver of social inequality, not a defender of social equity. As one wise sage said: Equality among unequals is inequitable. Thus, Constitutions don’t make revolutions. Revolutions make Constitutions. Liberal ideology extols human rights while in the same breath exorcising it of human freedom. We constantly hear the Establishment rant that there are no rights without limits, just as there is no freedom without restraint. The powers-thatbe and their intellectuals ceaselessly preach what they present as the obvious truth: that rights without limits and freedom without restraint equal anarchy. If that was so obvious, why do they have to drum it in our ears all the time? The truth is that it is neither obvious nor true. There is no example in human history of an anarchical society. Organised human societies have always developed customs and mores and obligations to co-operate to produce their livelihoods and reproduce their kind, even though they may not have the language of rights and enforcers of ‘law and order’. It is in class societies that rights are given to appease and then taken away in limitation clauses. Resistance to dominant classes is considered ‘anarchical’. Law and order must be maintained and enforced. The question is: Whose law and which social order? The answer is: Bourgeois law and capitalist social order. That is not an obvious answer because it is not part of the dominant common sense. What is common sense, what is rational sense, and what is truth and nontruth, are all dictated by hegemonic ideologies. We are exposed to hegemonic ideologies from the cradle to the grave—in educational institutions and in the media, in the churches and mosques, in the harangues of politicians and in the homilies of preachers, in the articulations of professors and discourses of professionals, in the activism of NGOs and the admonition of GONGOS (Government Organised NGOs). The hegemonic ideology tells us law is neutral, justice is impartial and democracy is universal. The hegemonic ideology raises the spectre of anarchism and instability to plant the fear of freedom in the minds of the oppressed and the dominated classes. The fear of freedom is thus internalised by the working people and even middle classes. Middle classes (including elite intellectuals like us) also suffer from the fear of freedom because they want stability and certainty in their lives. They fear losing their place and status in society. They thus become ardent advocates of placing limits on the freedom of the working people, whom they consider unruly masses. But hegemonies are not given. They are not static. They need to be produced and reproduced all the time because underlying an ideology are social struggles of different classes and groups and the human struggle for freedom. These in turn produce counter-hegemonies that question the dominant common sense, just as underlying social forces question relations of power and production. Our intellectual discourses, too, are not independent of struggles. As producers and purveyors of ideas, we intellectuals are also engaged in the production of hegemonic and counter-hegemonic discourses, as I am now doing. Whether I am championing or challenging hegemonic ideas, I leave it to you to judge, since one of the hegemonic legal precepts tells me, ‘You cannot be a judge in your own cause’. In sum, law does matter. Constitutions do matter. They matter because in liberal democracies, or those that pretend to be so, legal and constitutional discourses are significant terrains of struggle in the process of production and reproduction of hegemonies and counter-hegemonies. It behoves counter-hegemonic intellectuals to join issues with hegemonic legal and constitutional discourses. I return to this point in Part III of my lecture. That brings me to another profound line in ‘The Internationale’: ‘That the thief returns his plunder’. The capitalist-imperialist thief has been plundering the African continent for the last five centuries. What does it mean in the African context for the thief to return his plunder? ‘The thief return his plunder’ is precisely what has underpinned and informed our struggles and discourses on national liberation and freedom, nation-building, postcolonial development and democracy. I address this in the next part of my lecture. Part II: Freedom and National Liberation Liberation from oppression and tyranny of foreign rule is a condition for freedom, not freedom itself. When we fought to free ourselves from colonialism, we were fighting for freedom, for uhuru: freedom to govern ourselves and freedom to make our own decisions. Leaders of liberation movements mobilised their people to fight for freedom—freedom from subservience to foreign power, freedom to reclaim our history, as Amilcar Cabral would put it, and freedom to develop our productive forces. For Cabral, independence was a necessary but not a sufficient condition for freedom. For him, independence only meant a national liberation movement in power which had to continue the struggle against imperialism to free completely the development of national productive forces (Cabral 1979). The translation of the national liberation struggle against colonialism into the language of rights as the right to self-determination is thus a poor rendering of the essence of the struggle for freedom. To repeat, the national liberation struggle is to reclaim history, to set free the development of national productive forces, thus creating conditions for the flowering and enjoyment of all fundamental freedoms. After liberation and revolution, the original cause of the struggle, freedom, gets quickly buried in the exigencies of building the nationstate and developing the country. Different social classes and groups in the struggle for uhuru had their own different conceptions of freedom and development after independence. The tensions, the contradictions and the struggles of different conceptions of freedom are best summed up in the age-old philosophical dilemma between freedom and necessity. The nationalist’s sense of freedom was to be free to build the nation from the rubble of racial, ethnic and religious divisions planted by colonialists. Nyerere declared poverty, disease and ignorance as the three main enemies. The medicine was development, rapid development. ‘We should run, while others walk’, he said. Nationalists like Kwame Nkrumah warned of the ‘thief’ walking out of the political door and coming back through the economic door. He called it neocolonialism. Uncompromising nationalists like Patrice Lumumba refused to make peace with departing colonialists. At the independence celebrations on 30 June 1960, King Baudouin of Belgium was first to speak, glorifying the work of the butcher Leopold II and hoping that the Congolese would prove worthy of the ‘confidence’ placed in them (Hochshild 1999: 334). Joseph Kasa Vubu, the president, followed with a grovelling speech praising the work done by the colonialists. Then followed Prime Minister Lumumba. He listed the bondage in which the Belgian colonialists had kept the Congolese for eighty years, dehumanising and humiliating them while plundering their lands and resources. ‘We have known sarcasm and insults, endured blows morning, noon and night …,’ said Lumumba. He added that the wounds inflicted were too fresh to be forgotten (De Witte 2001: 2). For listing the crimes of the colonialists and enumerating the booty that the thief had extracted, Lumumba paid with his life. Through the connivance and conspiracy of Belgian officers and CIA operatives, with the UN’s tacit approval, Lumumba was tortured and killed by a firing squad. His body was dissolved in sulphuric acid supplied by Union Manière so it would never become a shrine for future generations (ibid.: 140 et seq). Lumumba’s fate was a lesson to the rest of Africa: ‘Dare you challenge … Fall in line or else…’. Nationalists like Nkrumah who did not fall in line were overthrown. Compradors like Jomo Kenyatta who ‘forgot and forgave’ survived, sharing the booty of the ‘thief’. In between, moderates like Nyerere negotiated their survival. Compromising here, confronting there, but always making sure that nationalists and compradors, progressives and reactionaries would, all alike, be kept in the fold of the party-state to deny imperialists an organised base from which to operate. In the process, freedoms, in particular collective freedoms like the right to organise, were sacrificed. To build the nation-state, national unity was necessary. For the nation-state to survive, its security could not be allowed to be undermined. Which meant individual freedom was sacrificed. Necessity trumped freedom. When Mwalimu was asked by Bill Sutherland (some time after Mwalimu had stepped down) whether preventive detention was still necessary, he said: ‘Yes—the quick answer is yes. Once you have accepted the nation-state, you accept the consequences —including the armies, including security services, bureaucracy, police and the lot.’ He continued: ‘I do accept the rule of law and the courts.’ But ‘no nation has found that when the security of the state is threatened, the court system is enough. … When they feel the security of the nation is threatened, they lock people up’ (Interview in Sutherland and Meyer 2000: 87). At the abstract level, intellectuals can philosophise over the dilemma or the tension between freedom and necessity and it sounds innocuous. But the real question, which is political, is this: Who draws the line between freedom and necessity? Who determines where freedom ends and necessity begins? And the answer to that is political, not philosophical, and is not that innocuous, either. It is the balance of forces in the underlying class struggles, if you like, that is ultimately decisive and yet never final because the struggle for freedom is never final. As I opined at the beginning, democracy-as-freedom is not an end game; it is a process of struggle best described as democratisation. No one has captured democratisation as a struggle more aptly than Mwalimu himself. In 1978, students of this university demonstrated, protesting against the hikes in salary and benefits of parliamentarians. They marched through the working-class areas of Manzese and Magomeni. FFU (fanya fujo uone) was sent to stop the demonstration. Students were beaten, the university was closed, and lorries ferried them back to their homes. After the students were forgiven by Chancellor Mwalimu Nyerere, he visited the campus to have an informal conversation with the academic community. Mwalimu’s introductory remarks were on democracy. During question time, one student asked him something to this effect: ‘Mwalimu, you have spoken a lot about democracy, but when, the other day, we demonstrated, you sent the FFU to beat us up.’ Nkrumah Hall went totally silent. Mwalimu stared at him for a few moments, and then began his answer: ‘You know I am the head of state. And you know what the state means. It has the monopoly of violence. If you demonstrate in the street, of course, I’ll send the FFU. Does that mean you shouldn’t fight for democracy! No one will give you democracy on a silver platter.’ (from memory) We all applauded. Mwalimu could have his cake and eat it. *** Let me now briefly discuss the intellectual debates on development and democracy during the three decades of post-independence Africa. In the sixties, seventies and eighties, before the neoliberal virus infected us, there were spirited discussions among African intellectuals on development and democracy. Some of the arguments are best captured in the debate between two of our colleagues, Peter Anyang’ Nyong’o from Kenya and the late Thandika Mkandawire from Malawi. Peter argued that democracy was a necessary condition for development. Without democracy Africa could not develop. Thandika shot back saying that Peter’s was an instrumentalist view of democracy. Indeed, in Africa we deserved democracy because democracy was good in itself. I may have oversimplified, nonetheless I think I have caught the essence of Peter’s and Thandika’s positions (see Nyong’o 2020 and references cited in there). I made a short intervention called ‘Pitfalls in the Debate on Democracy’. My submission was that Peter’s position was economistic while Thandika’s moralistic. Neither captured the social character nor the social struggles that underlie ‘development’ and ‘democracy’. Both ‘development’ and ‘democracy’ were terrains of struggle. I projected that what was likely to result from the then ‘wave of democratisation’ (remember, this debate happened in the late eighties and early nineties) would be neither liberal nor national democracy, but rather ‘compradorial democracy’ (Shivji 1989). Peter Nyong’o was disappointed and Ibbo Mandaza somewhat irritated by my intervention. The late Archie Mafeje came to my rescue. Mafeje was one of the most profound and theoretically grounded African intellectuals. He read African scholars and intellectuals closely, joined issues and critiqued them without mincing his words. On my concept of ‘compradorial democracy’, Mafeje commented that it ‘might be etymologically vulgar and theoretically undeveloped but, as a shorthand for what is happening or likely to happen in Africa under the current pax Americana, it hit the nail on the head’ (Mafeje 1995: 25). In the last thirty years of neoliberalism since this was written, we have indeed witnessed the rise of new compradors who are incapable of playing by the rules of ‘liberal’ democracy, much less national democracy. Now, in the current period, we are witnessing in some places the rise of narrow nationalists and populist demagogues, still in the shadow of neoliberalism, who do not pay even lip-service to liberalism or care for people’s fundamental freedoms. Before I end this Part let me return to the central problematique of this lecture. Democracy, and development, for that matter, are terrains of struggle for freedom. You might recall the title of Amartya Sen’s book, Development as Freedom (1999). He was not the first to say it. Mwalimu had said it many years before Sen. In a 1968 policy paper on ‘Freedom and Development’, Mwalimu argued that freedom and development were ‘linked together as are chickens and eggs! Without chickens you get no eggs; and without eggs you soon have no chickens. Similarly without freedom you get no development, and without development you very soon lose your freedom’ (Nyerere [1968] 1973: 58). He underlined three aspects of freedom. First, national freedom to make your own decisions without interference from outside. Second, freedom from hunger, disease and poverty, that is, freedom from necessity. And third, freedom of the individual ‘to live in dignity and equality’. A person’s ‘right to freedom of speech, freedom to participate in the making of all decisions which affect his life, and freedom from arbitrary arrest because he happens to annoy someone in authority…’, are sacrosanct, Mwalimu emphasised (ibid.). More to the point for this lecture is Mwalimu Nyerere’s speech to Maryknoll Sisters in 1970. The thrust of his argument was that the ‘development of peoples means rebellion’ (Nyerere [1970] 1973: 215). Development means to rebel against unjust social and economic structures that condemn people to unfreedom. It is from this argument that we derived the title of Mwalimu’s biography published last year: Development as Rebellion (Shivji et al. 2020). I end this part by defining development as a terrain of struggle to expand the realm of freedom and restrict the tyranny of necessity. And that brings me to turn the searchlight on ourselves, the intellectuals. Part III: Freedom and Intellectuals What role do we intellectuals play in the struggle to expand the vistas of freedom against the forces of unfreedom in all its three senses that Mwalimu talked about? Imperialism, in its varied reincarnations, is clearly the first force of unfreedom against national freedom to make our own decisions. Capital is the second force of unfreedom, which produces and reproduces social relations of production and power relations of domination that keep the large majority of working people and middle classes in oppressed and exploited conditions. Authoritarianism, and now increasingly jingoistic and protofascist regimes, is the third force of unfreedom, which tramples on fundamental freedoms and human dignity. The forces of unfreedom do not rule by coercion alone, though coercion is always present underneath the surface of consensus. Dominant classes and social groups have their sets of ideas or ideologies, they have their worldview and vision, and they have their social and cultural practices. They believe these to be true for all peoples at all times, although ultimately these ideologies rationalise, justify and legitimise the status quo, which serves dominant interests. But dominant ideologies are not constant, they are not cast in stone nor are they free of contradictions. They change and have to be constantly reproduced to accommodate the challenges they face. There is thus a constant struggle of ideas, a clash of ideas, if you like. One of the most important sites of the struggle of ideas is the university. It is not the only site but I’ll focus on this site for today’s lecture. We, university intellectuals, are not the only intellectuals. Gramsci said that all men and women in society are intellectuals because ‘people think’ but not all perform the social function of intellectuals in their social capacity. So, not all fall in the professional category of intellectuals (see, generally, Giroux 1985). Thus, we have a special social category that we call intellectuals but we do not have non-intellectuals. Intellectuals work with ideas. We produce ideas that justify, rationalise and legitimise the political, cultural and social practices of the dominant system. We also produce ideas that question, challenge and critique dominant ideas. Our intellectual work is not isolated or distinct from power and culture, controversies and clashes, and the social struggles happening all around us. A common phrase used for universities is ‘ivory tower’. Sometimes it is used in a derogatory sense. ‘These thinkers are not doers; they are too theoretical, too abstract,’ we are often chided. Sometimes the phrase is used in a complimentary sense, to signify the work of a university as objective and scientific and therefore unbiased. In whatever sense the phrase ‘ivory tower’ is used, the truth is that it is related to the ivories of the wild and the towers of the town. The gown and the town are not independent of each other. We must therefore acknowledge that the knowledge we produce is neither neutral nor apolitical. Giroux (1985) identifies four categories of intellectuals. One of them he calls critical intellectuals. These are intellectuals who are critical but do not see themselves as political nor do they acknowledge that their work is related to and not distinct from the society in which they exist. In short, this category of intellectuals sees themselves as free floating, decontextualised and delinked from the town. Giroux’s other three categories are accommodating intellectuals, hegemonic intellectuals and resisting intellectuals. Accommodating intellectuals, as the name suggests, support the status quo. They produce ideas and social practices that uncritically advance the interests of the dominating classes while all the time denying that they are political. They swear by professionalism while pleading agnosticism and ignorance of the struggles going on in their societies. My guess is that accommodating intellectuals perhaps form the largest group in terms of numbers, even though their social impact is in inverse proportion to their numbers. Hegemonic intellectuals are conscious agents of dominant classes. They provide ideas to give coherence to factions of dominating classes. They propagandise for the system while at the same time giving dominant classes selfawareness of their interests. ‘Such intellectuals’, Giroux says, ‘are to be found on the consulting lists of major foundations, on the faculties of major universities as managers of the culture industry, and in spirit at least in teaching positions at various levels of schooling’ (Giroux 1985: 89). Hegemonic intellectuals, as donors’ consultants, played a significant role in this country in the transition from radical nationalism to rampant neoliberalism. And their brethren in the administration equally played a critical role in the neoliberalisation and marketisation of this university. Their role in suppressing radical ideas and debates on this campus cannot be gainsaid. The fourth category is what Giroux calls resisting intellectuals and what I like to call antior counter-hegemonic intellectuals. This group joins issues with hegemonic intellectuals by challenging and questioning hegemonic ideas. They are not only most critical and analytical but also consciously produce alternative ideas and ideologies to provide articulation and coherence to dominated classes and their struggles. They do what Mao Tse-Tung once said: ‘We must teach the masses clearly what we have received from them confusedly’ (quoted in Freire [1970] 1993: fn.7, 93). They are motivated by passion for justice and freedom to create a new world, a civilised world far from the five centuries of capitalist barbarism. Once upon a time, a generation ago, such a category of intellectuals took this campus by storm. We saw audacious debates. We saw questioning students and challenging faculty. As researchers we produced some original works. We did not take lock, stock and barrel theories fed to us by the hegemonic intellectuals of the North. The University of Dar es Salaam became known far and wide for researching our concrete reality, for critical analysis and relevant theorising. Resisting intellectuals were small in number but their impact was big. They provided intellectual leadership and led the struggle to democratise the bureaucratic structures of the university. Then came the neoliberal attack. It was vicious and devastating. The likes of the World Bank told us that Africa did not need thinkers, they needed doers. When they sensed resistance, they changed their slant. ‘Vocationalise your curricula to make your products marketable. Commodify and privatise education’, they advised. Starved of resources, hegemonic administrators bought the prescription. They set to neoliberalise this university, just like the country. They changed the university from a site of democratic struggles in the public sphere to a private marketplace of consumers and clients. Once, I heard a senior academic in the Senate saying that we, the university, were like a factory. We must learn how to package our products, meaning students, to make them saleable. And lo and behold! Well-funded ToTs (training of trainers) followed to teach our administrators how to package and brand their products to make them marketable. I know I will be told I am oversimplifying, I am caricaturing. That the story is much more complex. That it was necessary to make changes to survive. Of course the story is complex! Which story is not? Of course there are at least two narratives—the narrative of necessity and the narrative of freedom. But isn’t that precisely the message of my caricaturing? That there is a struggle between hegemonic and counter-hegemonic ideas in which intellectuals are involved. Hegemonic intellectuals tell the story of necessity and they present it as the only rational, common-sense story. Counter-hegemonic intellectuals tell the story of freedom. They fully recognise that there is the other story—the story of necessity—and join in battle with it. That is precisely the social function of resisting intellectuals. Now, I am told that the species called resisting intellectuals is almost extinct on the Hill. A few have been hunted down; some have been poached by the powersthat-be and others have metamorphosed into policy consultants and advisers of IFIs (International Financial Institutions). Neoliberalism is triumphant. But the triumph of neoliberal ideas is episodic. The struggle for freedom, as I said right at the beginning, is epochal. I am an incorrigible optimist. Neoliberalism and its accompanying fascism, which suppresses people’s freedom, will pass. Maybe it is already passing. The struggle for human freedom is indomitable. Ideas of freedom are resurrecting. When we get an insurrection of freedom ideas, no force on Earth can stop it. I can do no better than end my lecture with a quote from Mwalimu Nyerere. Mwalimu was an enigmatic figure. He combined in himself a pragmatic, albeit ethical, politician and a principled intellectual. Either way his message was always profound. Responding to his friend from Yugoslavia who expressed despondency about the wars going on in his country, Yugoslavia, Mwalimu said: You are among the many people who have spent your life engaged in trying to expand the boundaries of human freedom in its widest sense. That territory is by definition unmapped; none of us miss all the obstacles in it! And often we find that some of those who had accepted our leadership get tired of the struggle forward and succumb to the temptations of those who promise benefits for not struggling—or short cuts such as religious fundamentalism, nationalism, or fascism. ‘… those who… get tired of the struggle forward … succumb to the temptations of those who promise benefits for not struggling—or short cuts such as religious fundamentalism, nationalism, or fascism’… That rings a bell, doesn’t it? Need I say more? The progress of mankind ebbs and flows like the tides, but we are further forward in decency and civilisation than when Homo Sapiens first emerged, despite all the horrors at any one time—including the present. As individuals, as family and friendship units, and as companions in the pursuit of ideas and ideals which have been built upon the struggles of others, we are victims. But it seems to me that eventually there will truly be One World. The underlying movement is in that direction. (Quoted in Shivji et al. 2020: Book 1, xix-xx) Like all socialists, Mwalimu was thinking of epochs not episodes. Mr. Vice-Chancellor and my dear colleagues, I end as I began. The struggle for human freedom is epochal not episodic. One day, all humankind will meet at the rendezvous of victory and sing with Martin Luther King: Freedom at last! Freedom at last! Then the barbaric capitalist system will appear in children’s story books as an example of a gruesome episode in the march of humankind to freedom. Notes This lecture was delivered on 1 July 2021 at the Mwalimu Nyerere Intellectual Festival organised by the Mwalimu J K. Nyerere Professorial Chair in Pan-African Studies (Kigoda cha Mwalimu as it is popular known in Swahili; and the holder of the Chair is called Nyagoda), University of Dar es Salaam. https://www.ihaveadreamspeech.us/ https://malcolmx.com/quotes/ https://www.goalcast.com/2018/01/01/frederick-douglass-quotes/ The Internationale was written by Eugène Pottier in Originally written in French there are numerous English versions. I have quoted from the one at https://en.wikipedia.org/wiki/The_Internationale